ANALYSIS OF A DATABASE REPLICATION ALGORITHM UNDER LOAD SHARING IN NETWORKS - SANJAY KUMAR YADAV; GURMIT SINGH; DIVAKAR SINGH YADAV (Journal of Engineering Science and Technology, 2016)
Recently, (PDDRA) a Pre-fetching based dynamic data replication algorithm has been published. In our previous work, modifications to the algorithm have been suggested to minimize the delay in data replication. In this paper, a simulation framework is presented and results are obtained to estimate the throughput and average delay. The overall network is divided into two parts as local and global networks. The data requests are generated only at the local nodes. However, the service can be obtained form both local and global servers. In our previous work it has been found that the throughput and average delay heavily depends on buffer capacity of sever node and if server load is below 80% then, nearly 100% throughput is possible with very small average delay. In this paper, we have shown that shown the delay can be further minimized by sharing the load among servers, still throughput remains nearly 100 percent.